ANALISIS PENERAPAN MODEL PEMBELAJARAN VAK (VISUALISASI, AUDITORI, KINESTETIK) DALAM MENINGKATKAN PEMAHAMAN KOGNITIF SISWA KELAS V B PADA PEMBELAJARAN IPAS DI SDN 131/IV KOTA JAMBI. - Permadi, Dika; Mislan, Mislan; Viktoria, Jetra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the application of the VAK (Visual, Auditory, and Kinesthetic) learning model in improving the cognitive understanding of fifth grade B students in IPAS subjects at SDN 131/IV Kota Jambi. This study uses a qualitative approach with a descriptive research type. The research subjects consist of fifth grade B teachers and fifth grade B students. Data collection techniques were conducted through observation, in-depth interviews, and documentation. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the application of the VAK learning model is able to create more varied learning, increase student involvement, and help students understand IPAS material through learning experiences that are in accordance with their learning styles. The visual factor helps students understand concepts through pictures and media, the auditory factor strengthens understanding through explanations and discussions, while the kinesthetic factor helps students understand concepts through practical activities. Thus, the application of the VAK learning model contributes positively to improving students' cognitive understanding.